A Complex Case of Rhupus Syndrome with Vogt-Koyanagi-Harada Syndrome in a Patient with Type 2 Diabetes Mellitus: A Therapeutic Challenge and Multidisciplinary Approach - Jayeshbhai, Vaghani Krunal; Krishnan, Shanmuganandan; N. Anuradha, N. Anuradha (Journal of Neonatal Surgery, 2025)
Vogt-Koyanagi-Harada Syndrome (VKH) syndrome is a autoimmune disorder affecting melanin-pigmented tissues, with significant ocular manifestation, ear, skin, and central nervous system. We report a rare patient with a VKH Associated With Rhupus syndrome. Case Report 49-year-old lady with a history of type 2 diabetes mellitus presented with abdominal pain, breathlessness, and visual impairments. Diagnostic evaluation confirmed VKH syndrome, characterized by bilateral diffuse uveitis and other systemic involvements.. Further investigations revealed an overlap syndrome of SLE and RA, commonly known as Rhupus syndrome, complicating her clinical course. The patient was treated with intravenous methylprednisolone, mycophenolate mofetil, and oral prednisone, leading to significant improvement in ocular symptoms and visual acuity Conclusion This case underscores the complexity of diagnosing and managing patients with multiple overlapping autoimmune disorders.